TINJAUAN STRATEGI DIGITAL RUPIAH UNTUK MENGUNGKAP PELAKU MONEY LAUNDERING - Diva Syafira, (2023)
At this time the Minister of Home Affairs (Mendagri), revealed a new mode of money laundering, namely by carrying cash, this effort was made by money laundering actors to avoid monitoring and detection from the Financial Transaction Reports and Analysis Center (PPATK) and law enforcers. Therefore, the Indonesian government has planned to develop a Central Bank Digital Currency (CBDC) system by launching a Digital Rupiah plan as a new solution to overcome this problem. Not only Indonesia, other countries have also started this research. One of them is China, with its E-CNY as a reference for research on the potential of Digital Rupiah because China has started this research since 2016 and has implemented its E-CNY since 2019. Not only that, E-CNY has also succeeded in uncovering money laundering actors. This study aims to find out the results of the analysis of Digital Rupiah plans as a new solution to uncover money laundering actors with cash transactions. This study uses an observational descriptive analysis method. The data used comes from official government documents, official world bank documents, PPATK reports, and previous research journals both from within and outside the country. The results of the analysis show that the Digital Rupiah plan has almost the same technology and features as E-CNY so that Digital Rupiah is able to become a new solution in uncovering money laundering actors.